Zinc-aluminum-magnesium high-strength if steel for automobile outer plate and preparation method thereof

CN122979767APending Publication Date: 2026-10-27SHOUGANG JINGTANG IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611125635.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,针对含磷、锰、硅的高强IF钢表面缺陷问题,目前行业内的解决方案尚不完善

Benefits of technology

本申请实施例提供了一种用于汽车外板的锌铝镁高强IF钢及制备方法,所述锌铝镁高强IF钢包括钢基体和附着于所述钢基体至少部分表面的锌铝镁镀层;其中,以质量分数计,所述钢基体的化学成分为:C≤0.003%,Si≤0.008%,Mn:0.90%~1.30%,P:0.050%~0.085%,S≤0.015%,Nb:0.010%~0.045%,Ti:0.01%~0.04%,Als:0.025%~0.045%,其余为Fe及不可避免的杂质;以质量分数计,所述锌铝镁镀层的化学成分为:Al:1%~3%,Mg:1%~3%,其余为Zn及不可避免的杂质;所述钢基体表面具有通过预氧化段形成的氧化铁层,所述氧化铁层抑制P和Mn向所述钢基体表面迁移,并促进所述锌铝镁镀层与所述钢基体形成Fe-Al结合层。在钢基体成分设计方面,将C含量严格控制在0.003wt%以下,并添加适量的Al,利用Al固定钢基体中的间隙碳原子和间隙氮原子,形成碳氮化物,从而获得纯净的铁素体基体。通过添加0.050wt%~0.085wt%的P和0.90wt%~1.30wt%的Mn进行固溶强化,是实现440MPa级以上高强度的关键手段。然而,P和Mn在退火过程中易向表面偏聚,形成微观缺陷,直接恶化表面质量。为解决P和Mn偏聚带来的表面质量问题,将Si含量限制在极低的0.008wt%以下,从根本上消除了硅氧化物导致的镀层附着不良和表面粗糙问题。采用0.010wt%~0.045wt%的Nb与0.01wt%~0.04wt%的Ti进行复合微合金化。Nb和Ti形成的细小、弥散碳氮化物不仅提供显著的析出强化效果以补充强度,还能有效钉扎晶界、细化晶粒,并抑制再结晶晶粒的异常长大,从而获得均匀、细小的微观组织。同时,Ti能进一步固定残余的碳原子,Nb能延缓再结晶过程,Ti和Nb协同促进有利织构的发育,进一步提升锌铝镁高强IF钢的深冲性能。在锌铝镁镀层成分设计方面,Al的加入能在热浸镀过程中与洁净的钢基体表面优先反应,形成一层连续、致密且附着牢固的Fe-Al金属间化合物层。Fe-Al金属间化合物层是镀层与钢基体实现强冶金结合的核心,能有效防止镀层在冲压变形过程中脱落或粉化。Mg的加入能细化镀层组织,抑制脆性相的生长,并在腐蚀初期形成致密的保护膜,显著提升镀层的耐蚀性。Al和Mg的特定比例优化了镀液的流动性与润湿性,使得镀层在凝固结晶时更加均匀、平整,有助于覆盖钢基体微观不平整处,从而获得光滑、细腻的表面外观。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979767A_ABST
    Figure CN122979767A_ABST
Patent Text Reader

Abstract

The application relates to a zinc-aluminum-magnesium high-strength IF steel for automobile outer plates and a preparation method, and belongs to the technical field of steel material preparation. The zinc-aluminum-magnesium high-strength IF steel comprises a steel matrix and a zinc-aluminum-magnesium plating layer attached to at least part of the surface of the steel matrix; wherein the chemical composition of the steel matrix, in terms of mass fraction, is as follows: C<=0.003%, Si<=0.008%, Mn: 0.90%-1.30%, P: 0.050%-0.085%, S<=0.015%, Nb: 0.010%-0.045%, Ti: 0.01%-0.04%, Als: 0.025%-0.045%, and the rest is Fe and inevitable impurities; and the chemical composition of the zinc-aluminum-magnesium plating layer, in terms of mass fraction, is as follows: Al: 1%-3%, Mg: 1%-3%, and the rest is Zn and inevitable impurities. By optimizing the design of strengthening elements such as P, Mn, Nb and Ti, the high strength and high formability of the steel matrix are ensured. The pre-oxidation process is adopted in the continuous annealing section to generate an iron oxide layer, inhibit the migration of P and Mn to the surface, and promote the formation of an Fe-Al bonding layer between the plating layer and the steel matrix. By utilizing the corrosion resistance and lubricity of the zinc-aluminum-magnesium plating layer, the zinc-aluminum-magnesium high-strength IF steel with high surface quality for automobile outer plates is finally obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of steel material preparation technology, and in particular to a zinc-aluminum-magnesium high-strength IF steel for automobile outer panels and its preparation method. Background Technology

[0002] With the automotive industry trending towards lightweighting and high-end products, steel used for automotive outer panels must simultaneously meet the comprehensive requirements of high strength, excellent formability, high surface quality, and superior corrosion resistance. Traditional high-strength IF steel is often strengthened by adding elements such as phosphorus, manganese, and silicon. However, excessive phosphorus content can impair the toughness and weldability of high-strength IF steel, while excessive manganese content can significantly degrade its plasticity and stamping formability. Silicon readily reacts with the plating solution during hot-dip galvanizing to form brittle compounds, resulting in a rough surface and weakened coating adhesion. When using zinc-aluminum-magnesium coatings with superior corrosion resistance, the surface defects of high-strength IF steel containing phosphorus, manganese, and silicon become even more pronounced. These surface defects severely restrict the application of high-strength IF steel containing phosphorus, manganese, and silicon in the high-end automotive outer panel sector.

[0003] However, current industry solutions for surface defects in high-strength IF steel containing phosphorus, manganese, and silicon are still incomplete. For example, one technology involves pre-oxidation through humidification in the annealing heating zone, but the high dew point control range easily leads to over-oxidation, and the oxidizing atmosphere may diffuse into the subsequent reduction zone, causing cracks in the subsurface layer of the steel substrate and affecting the performance of high-strength IF steel. Another technology uses a silicon-containing composition design combined with a traditional zinc-iron alloy coating, which carries the risk of silicon-induced surface enrichment and decreased coating adhesion. Meanwhile, the single-titanium strengthening design has limited effectiveness in precipitation strengthening and aging inhibition, and the corrosion resistance and lubricity of the zinc-iron alloy coating are inferior to those of the zinc-aluminum-magnesium coating. Summary of the Invention

[0004] This application provides a zinc-aluminum-magnesium high-strength IF steel for automotive outer panels and its preparation method, in order to solve the following technical problem: how to ensure that the zinc-aluminum-magnesium high-strength IF steel has high surface quality. In a first aspect, embodiments of this application provide a zinc-aluminum-magnesium high-strength IF steel for automotive outer panels, the zinc-aluminum-magnesium high-strength IF steel comprising a steel substrate and a zinc-aluminum-magnesium coating attached to at least a portion of the surface of the steel substrate; The chemical composition of the steel matrix, by mass fraction, is as follows: C≤0.003%, Si≤0.008%, Mn: 0.90%~1.30%, P: 0.050%~0.085%, S≤0.015%, Nb: 0.010%~0.045%, Ti: 0.01%~0.04%, Als: 0.025%~0.045%, with the remainder being Fe and unavoidable impurities. The chemical composition of the zinc-aluminum-magnesium coating, by mass fraction, is: Al: 1%~3%, Mg: 1%~3%, with the remainder being Zn and unavoidable impurities; The steel substrate surface has an iron oxide layer formed by a pre-oxidation section. The iron oxide layer inhibits the migration of P and Mn to the steel substrate surface and promotes the formation of an Fe-Al bonding layer between the zinc-aluminum-magnesium coating and the steel substrate.

[0005] Optionally, the microstructure of the zinc-aluminum-magnesium high-strength IF steel includes a ferrite matrix and Nb(C,N) and TiC carbonitride precipitates dispersed in the ferrite matrix.

[0006] Optionally, the zinc-aluminum-magnesium high-strength IF steel meets at least one of the following properties: yield strength of 260MPa~300MPa, tensile strength of 400MPa~440MPa, and elongation after fracture A. 80 ≥33%, work hardening index ≥0.19, plastic strain ratio ≥1.85.

[0007] Secondly, embodiments of this application provide a method for preparing the zinc-aluminum-magnesium high-strength IF steel described in the first aspect, the method comprising: Molten steel with the following chemical composition is continuously cast to obtain a billet: C≤0.003%, Si≤0.008%, Mn: 0.90%~1.30%, P: 0.050%~0.085%, S≤0.015%, Nb: 0.010%~0.045%, Ti: 0.01%~0.04%, Als: 0.025%~0.045%, with the remainder being Fe and unavoidable impurities; The cast billet is sequentially heated, rough rolled, finish rolled, and coiled to obtain a hot-rolled coil. The hot-rolled coil is sequentially pickled and cold-rolled to obtain a cold-rolled hard coil; the total reduction rate of the cold rolling is 55%~80%. The cold-rolled coil is continuously annealed to obtain an annealed plate; the continuous annealing includes a pre-oxidation section, a heating section, a soaking section, a slow cooling section, a rapid cooling section, and an over-aging section; The annealed sheet is subjected to continuous hot-dip galvanizing, cooling and finishing in sequence to obtain zinc-aluminum-magnesium high-strength IF steel.

[0008] Optionally, the heating temperature is 1220℃~1260℃, and the total heating time is 180min~260min.

[0009] Optionally, the finishing rolling temperature is 910℃~950℃.

[0010] Optionally, the winding temperature is 580℃~650℃.

[0011] Optionally, the continuous annealing speed is 90 m / min to 120 m / min.

[0012] Optionally, the pre-oxidation section uses high-temperature steam, the dew point of the pre-oxidation section is -35℃ to -20℃, and the temperature of the pre-oxidation section is 650℃ to 750℃; The dew point (T) d The temperature (T) satisfies: Td = -(0.65 - 1.83) × 10 -8 T 3.3 .

[0013] Optionally, the temperature of the heating section is 750℃~790℃; the temperature of the heat spreader section is 750℃~790℃; the temperature of the slow cooling section is 670℃~690℃; the temperature of the rapid cooling section is 460℃~480℃; and the temperature of the over-aging section is 400℃~480℃.

[0014] Optionally, the temperature of the zinc pot during continuous hot-dip galvanizing is 440℃~460℃.

[0015] Optionally, the cooling is post-plating cooling, and the final temperature of the cooling is 250℃~270℃.

[0016] Optionally, the elongation of the finishing process is 1.3% to 1.5%.

[0017] The technical solutions provided in this application have the following advantages compared with the prior art: This application provides a zinc-aluminum-magnesium high-strength IF steel for automotive outer panels and its preparation method. The zinc-aluminum-magnesium high-strength IF steel includes a steel substrate and a zinc-aluminum-magnesium coating attached to at least a portion of the surface of the steel substrate. The chemical composition of the steel substrate, by mass fraction, is: C≤0.003%, Si≤0.008%, Mn: 0.90%~1.30%, P: 0.050%~0.085%, S≤0.015%, Nb: 0.010%~0.045%, Ti: The zinc-aluminum-magnesium (ZA) coating contains 0.01%~0.04% Al, 0.025%~0.045% Al, with the remainder being Fe and unavoidable impurities. The chemical composition of the ZA coating, by mass fraction, is: Al: 1%~3%, Mg: 1%~3%, with the remainder being Zn and unavoidable impurities. The steel substrate surface has an iron oxide layer formed through a pre-oxidation section. This iron oxide layer inhibits the migration of P and Mn to the steel substrate surface and promotes the formation of an Fe-Al bonding layer between the ZA coating and the steel substrate. In terms of steel substrate composition design, the C content is strictly controlled below 0.003wt%, and an appropriate amount of Al is added. Al is used to fix interstitial carbon and nitrogen atoms in the steel substrate, forming carbonitrides, thereby obtaining a pure ferrite matrix. Solid solution strengthening by adding 0.050wt%~0.085wt% P and 0.90wt%~1.30wt% Mn is a key method to achieve high strengths above 440MPa. However, P and Mn tend to segregate to the surface during annealing, forming microscopic defects and directly deteriorating surface quality. To address the surface quality issues caused by P and Mn segregation, the Si content is limited to an extremely low level of below 0.008 wt%, fundamentally eliminating the problems of poor coating adhesion and surface roughness caused by silicon oxides. Composite microalloying is performed using 0.010 wt%~0.045 wt% Nb and 0.01 wt%~0.04 wt% Ti. The fine, dispersed carbonitrides formed by Nb and Ti not only provide significant precipitation strengthening to supplement strength but also effectively pin grain boundaries, refine grains, and inhibit abnormal growth of recrystallized grains, thereby obtaining a uniform and fine microstructure. Simultaneously, Ti further fixes residual carbon atoms, and Nb delays the recrystallization process. Ti and Nb synergistically promote the development of favorable textures, further improving the deep-drawing performance of zinc-aluminum-magnesium high-strength IF steel. In the design of zinc-aluminum-magnesium (ZAM) coating composition, the addition of Al preferentially reacts with the clean steel substrate surface during hot-dip galvanizing, forming a continuous, dense, and firmly adhered Fe-Al intermetallic compound layer. This Fe-Al intermetallic compound layer is the core of the strong metallurgical bond between the coating and the steel substrate, effectively preventing the coating from peeling off or pulverizing during stamping deformation. The addition of Mg refines the coating microstructure, inhibits the growth of brittle phases, and forms a dense protective film in the early stages of corrosion, significantly improving the coating's corrosion resistance.The specific ratio of Al and Mg optimizes the fluidity and wettability of the plating solution, making the coating more uniform and smooth during solidification and crystallization. This helps to cover the microscopic unevenness of the steel substrate, thereby obtaining a smooth and delicate surface appearance.

[0018] In summary, the challenges posed by high surface quality requirements are systematically addressed through the synergistic chemical composition design of the steel substrate and the zinc-aluminum-magnesium (ZAM) coating. The steel substrate composition is characterized by ultra-low C, ultra-low Si, Nb, and Ti composite microalloying, ensuring high strength and excellent formability while striving to achieve a uniform, clean, and moderately reactive surface, creating optimal conditions for subsequent coating. The ZAM coating, with optimized Al and Mg content, provides corrosion resistance while ensuring excellent smoothness, uniformity, and adhesion. The combination of the steel substrate and the ZAM coating lays a solid foundation for achieving high-quality automotive exterior panel products. Attached Figure Description

[0019] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0020] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without any creative effort.

[0021] Figure 1 This is a flowchart illustrating a method for preparing zinc-aluminum-magnesium high-strength IF steel for automotive outer panels, as provided in an embodiment of this application. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0023] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values ​​within that range. For example, the range descriptions of "1 to 6" or "1~6" cover all sub-ranges between 1 and 6 (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6). Unless otherwise specified, the terms "including" and "contains" used herein mean "including but not limited to"; relational terms such as "first" and "second" are used only to distinguish different entities or operations and do not imply an actual order or relationship. "And / or" indicates that multiple situations can exist individually or simultaneously. Expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships mentioned herein, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained through commercial purchase or prepared using existing methods.

[0024] In a first aspect, embodiments of this application provide a zinc-aluminum-magnesium high-strength IF steel for automotive outer panels, the zinc-aluminum-magnesium high-strength IF steel comprising a steel substrate and a zinc-aluminum-magnesium coating attached to at least a portion of the surface of the steel substrate; The chemical composition of the steel matrix, by mass fraction, is as follows: C≤0.003%, Si≤0.008%, Mn: 0.90%~1.30%, P: 0.050%~0.085%, S≤0.015%, Nb: 0.010%~0.045%, Ti: 0.01%~0.04%, Als: 0.025%~0.045%, with the remainder being Fe and unavoidable impurities. The chemical composition of the zinc-aluminum-magnesium coating, by mass fraction, is: Al: 1%~3%, Mg: 1%~3%, with the remainder being Zn and unavoidable impurities; The steel substrate surface has an iron oxide layer formed by a pre-oxidation section. The iron oxide layer inhibits the migration of P and Mn to the steel substrate surface and promotes the formation of an Fe-Al bonding layer between the zinc-aluminum-magnesium coating and the steel substrate.

[0025] The positive effects of limiting the C mass fraction in the steel matrix to ≤0.003%: As the most crucial strengthening element in the steel matrix, C can achieve multiple beneficial effects through extremely low-concentration design. Extremely low C mass fraction completely avoids cementite precipitation, maximizing the cold plasticity, cold stamping formability, and cold bending formability of the steel matrix, thus resolving the contradiction between high strength and formability. It eliminates C segregation at grain boundaries and, combined with low-Si design, significantly reduces the cold brittleness and temper brittleness tendency of the steel matrix. It reduces the binding loss of C with microalloying elements (Nb and Ti), ensuring that Nb and Ti are fully precipitated in the form of carbonitrides, fully utilizing the microalloying effect. Furthermore, extremely low C mass fraction can also improve the weldability of the steel matrix, avoiding the formation of hard and brittle martensite in the weld heat-affected zone and reducing the risk of weld cracking. For example, the C mass fraction in the steel matrix can be 0.001%, 0.002%, 0.003%, etc.

[0026] The positive effects of limiting the mass fraction of Si in the steel matrix to ≤0.008%: Si's solid solution strengthening effect in the steel matrix is ​​second only to P. However, for galvanized automotive steel sheets, Si inhibits the densification of the Fe-Zn alloy layer and promotes the growth of loose phases, resulting in weaker bonding between the loose phases and the steel matrix, making the coating prone to peeling off during stamping. On the other hand, during the annealing stage, Si accumulates on the surface of the annealed sheet to form an amorphous SiO2 film. This SiO2 film blocks the reaction between the iron matrix and the zinc liquid, causing plating defects. Therefore, although Si can supplement P in terms of strength, a low-Si design is still chosen. For example, the mass fraction of Si in the steel matrix can be 0.002%, 0.004%, 0.006%, 0.008%, etc.

[0027] The positive effects of limiting the mass fraction of Mn in the steel matrix to 0.90%~1.30%: Mn is a fundamental solid solution strengthening element and a core element in balancing strength and toughness. The incorporation of manganese atoms into the ferrite lattice causes lattice distortion, which can increase the yield strength and tensile strength of the steel matrix without significantly reducing plasticity. Therefore, Mn is one of the main sources of strength in low-carbon steel. Furthermore, the solid solution effect of Mn can offset some of the decrease in plasticity of the steel matrix caused by phosphorus (P), thus balancing the strengthening effect of P and its tendency to embrittle. For example, the mass fraction of Mn in the steel matrix can be 0.90%, 1.00%, 1.10%, 1.20%, 1.30%, etc.

[0028] The positive effects of limiting the mass fraction of phosphorus (P) in the steel matrix to 0.050%~0.085%: P is a highly efficient strengthening element added for targeted alloying. Around an ultra-low C, low Si composition matrix, P maximizes its solid solution strengthening advantages, achieving high strength at low C levels, while also considering the formability and toughness of zinc-aluminum-magnesium high-strength IF steel. P is a core element in the strength design of zinc-aluminum-magnesium high-strength IF steel. For example, the mass fraction of P in the steel matrix can be 0.050%, 0.055%, 0.060%, 0.065%, 0.070%, 0.075%, 0.080%, 0.085%, etc.

[0029] The positive effect of limiting the mass fraction of sulfur (S) in the steel matrix to ≤0.015% is to minimize the quantity and size of sulfide inclusions such as MnS in the steel matrix. Sulfide inclusions, especially elongated MnS, extend along the rolling direction during hot rolling. In subsequent processes, hard inclusions such as MnS may be exposed on the steel matrix surface or become defect sources beneath the coating, leading to micro-pits, lines, or unevenness on the steel matrix surface, directly impairing surface finish and uniformity. For example, the mass fraction of S in the steel matrix can be 0.005%, 0.010%, 0.015%, etc.

[0030] The positive effects of limiting the mass fraction of Nb in the steel matrix to 0.010%~0.045%: As a core microalloying element, Nb enhances the strength of the steel matrix through both precipitation strengthening and grain refinement strengthening. Nb can inhibit austenite recrystallization, refine grains, and simultaneously improve the high-temperature strength, toughness, and weld heat-affected zone properties of the steel matrix. For example, the mass fraction of Nb in the steel matrix can be 0.010%, 0.015%, 0.020%, 0.025%, 0.030%, 0.035%, 0.040%, 0.045%, etc.

[0031] The positive effects of limiting the mass fraction of Ti in the steel matrix to 0.01%~0.04% are as follows: Ti is a strong carbide and nitride forming element. Ti can fix carbon and nitrogen atoms in the steel matrix, eliminate aging phenomena, and ensure cold forming stability. At the same time, Ti can refine grains, improve the strength and toughness of the steel matrix, and protect the weld heat-affected zone from embrittlement. For example, the mass fraction of Ti in the steel matrix can be 0.01%, 0.02%, 0.03%, 0.04%, etc.

[0032] Acid-soluble aluminum (Als): refers to the aluminum content in steel that dissolves in acid, including solid-solution aluminum and aluminum in AlN, but excluding aluminum in oxide inclusions such as Al2O3. The Als content reflects the effective aluminum content in the steel and plays a crucial role in fixing nitrogen atoms, forming AlN precipitates, and inhibiting grain growth. The positive effects of limiting the mass fraction of Als in the steel matrix to 0.025%~0.045% are as follows: Als combines with residual N in the steel matrix to form fine AlN precipitates. On the one hand, AlN precipitates effectively eliminate the damage of free nitrogen atoms to the formability of zinc-aluminum-magnesium high-strength IF steel, prevent strain aging, and ensure high formability; on the other hand, fine and dispersed AlN particles can inhibit abnormal growth of ferrite grains during annealing, promoting the acquisition of a uniform, fine equiaxed grain structure. For example, the mass fraction of Als in the steel matrix can be 0.025%, 0.035%, 0.045%, etc.

[0033] Fe is a matrix element, and the specific content / range of Fe can be obtained through the upper and lower limit formulas of the component, that is: The sum of the percentages of all components in a composition should equal 100%, and the content ranges of several components should meet the following conditions: the upper limit of a certain component + the lower limit of other components ≤ 100; the lower limit of a certain component + the upper limit of other components ≥ 100. Furthermore, the specific content of Fe is made up to 100% by the actual detected values ​​of the other chemical components mentioned above, together with any unlisted active elements and / or impurity elements, and Fe must constitute the absolute proportion as a matrix element.

[0034] The positive effects of limiting the Al mass fraction in zinc-aluminum-magnesium coatings to 1%~3% include: ensuring a strong and tough metallurgical bond between the coating and the steel substrate, and creating conditions for obtaining a smooth and even surface morphology. When the Al mass fraction is below 1%, it is difficult to form a sufficiently continuous Fe-Al layer, resulting in insufficient adhesion between the coating and the steel substrate; when the Al mass fraction is above 3%, it may lead to increased brittleness of the coating, affecting its processability and surface uniformity. For example, the Al mass fraction in zinc-aluminum-magnesium coatings can be 1%, 2%, 3%, etc.

[0035] The positive effects of limiting the mass fraction of Mg in zinc-aluminum-magnesium coatings to 1%~3% include: improved corrosion resistance and optimized microstructure. The addition of Mg refines the solidification structure of the coating, inhibits the formation of coarse zinc spangles and brittle intermetallic compound phases, thereby achieving a more uniform and dense microstructure. For example, the mass fraction of Mg in zinc-aluminum-magnesium coatings can be 1%, 2%, 3%, etc.

[0036] Zn is a matrix element, and the specific content / range of Zn can be obtained through the upper and lower limit formulas of the component, that is: The sum of the percentage content of each component in a composition shall equal 100%, and the content range of several components shall meet the following conditions: the upper limit of a certain component + the lower limit of other components ≤ 100; the lower limit of a certain component + the upper limit of other components ≥ 100. In addition, the specific content of Zn shall be made up to 100% by the actual detected values ​​of the other chemical components mentioned above and by any unlisted active elements and / or impurity elements, and Zn shall be the matrix element and account for the absolute proportion.

[0037] The zinc-aluminum-magnesium coating has a thickness of 5μm~12μm and a single-sided coating weight of 40g / m. 2 ~120g / m 2 .

[0038] Coating thickness design basis: (1) Corrosion resistance requirements: The outer panel of the car is required to be free of red rust for 10 years, with a corresponding coating thickness of ≥5μm (≥40g / m on one side). 2 ); (2) Stamping formability: If the coating is too thick (>12μm), it will reduce the bonding strength between the coating and the substrate, and the coating is prone to powdering during stamping; (3) Weldability: A coating thickness of ≤12μm can ensure the electrode life and weld quality of resistance spot welding; (4) Coating properties: The coating thickness is within the range of 5μm~12μm, and the weight of the phosphating film is 2.0g / m. 2 ~3.5g / m 2 The adhesion of the electrophoretic coating film is ≥5B.

[0039] Coating thickness control methods: The coating thickness is controlled by the air knife pressure (15kPa~35kPa) and the nozzle distance (5mm~12mm); The temperature of the plating bath (440℃~460℃) and the speed at which the strip enters the zinc pot (90m / min~120m / min) are controlled in a coordinated manner. The online X-ray thickness gauge monitors the thickness in real time, and the thickness deviation is controlled within ±1μm.

[0040] Microstructure of the coating: Surface layer: Zn-Al-Mg ternary eutectic phase, with a thickness of 60%~70%, hardness HV 80~120, providing corrosion resistance and lubrication; Intermediate layer: Fe-Al intermetallic compound layer (Fe2Al5), 0.5μm~2μm thick, provides metallurgical bonding between the coating and the substrate; Interface layer: Fe-Zn-Al ternary alloy layer, thickness ≤0.3μm, to inhibit the growth of brittle Fe-Zn phase.

[0041] In some embodiments, the microstructure of the zinc-aluminum-magnesium high-strength IF steel includes a ferrite matrix and Nb(C,N) and TiC carbonitride precipitates dispersed in the ferrite matrix.

[0042] The ferrite matrix has a grain size of 8μm to 15μm, a grain size grade of 9.0 to 10.5, a grain shape factor (aspect ratio) ≤1.5, and an equiaxedness rate ≥90%.

[0043] The carbonitride precipitates comprise Nb(C, N) and TiC, wherein: Nb(C,N) precipitates: size 5nm~15nm, areal density ≥50 precipitates / μm 2 They are mainly distributed on grain boundaries and dislocation lines, and play a role in pinning grain boundaries and inhibiting the growth of recrystallized grains. TiC precipitates: size 3nm~10nm, areal density ≥80 precipitates / μm 2 They are mainly distributed within the crystals and play a role in fixing interstitial carbon atoms and eliminating strain aging. Composite precipitates (Nb, Ti) (C, N): size 8nm~20nm, distributed at the grain boundary triangulation points, strengthening the grain boundary bonding force.

[0044] The texture characteristics of the ferrite matrix are as follows: γ fiber texture ({111} / / ND) strength ≥ 3.5 × random, α fiber texture ({001} / / RD) strength ≤ 1.2 × random, and γ / α texture ratio ≥ 2.9, ensuring excellent deep drawing performance.

[0045] In some embodiments, the zinc-aluminum-magnesium high-strength IF steel satisfies at least one of the following properties: yield strength of 260MPa~300MPa, tensile strength of 400MPa~440MPa, and elongation after fracture A. 80 ≥33%, work hardening index ≥0.19, plastic strain ratio ≥1.85.

[0046] Yield strength: The stress value at which a material begins to undergo significant plastic deformation. A yield strength of 260MPa~300MPa indicates that zinc-aluminum-magnesium high-strength IF steel can maintain elasticity under high stress and has a strong ability to resist initial permanent deformation. For example, yield strengths can be 260MPa, 270MPa, 280MPa, 290MPa, 300MPa, etc. Tensile strength: The maximum stress value that a material can withstand before tensile fracture. A tensile strength of 400MPa~440MPa ensures that zinc-aluminum-magnesium high-strength IF steel can absorb more energy before severe deformation or even fracture, providing higher safety reserves and impact resistance for automotive body structures. For example, tensile strengths can be 400MPa, 410MPa, 420MPa, 430MPa, 440MPa, etc. Elongation after fracture: The percentage of permanent elongation of the material after fracture relative to the original gauge length. Elongation after fracture A 80 ≥33% means that zinc-aluminum-magnesium high-strength IF steel can withstand significant shape changes during stamping without premature cracking. For example, the elongation after fracture A... 80 The work hardening index can be 33%, 35%, 37%, 39%, etc. Work hardening index: A parameter describing the rate of strength increase during plastic deformation. A work hardening index ≥ 0.19 promotes uniform deformation diffusion in zinc-aluminum-magnesium high-strength IF steel, preventing necking and early fracture caused by strain localization, thereby improving the overall forming limit of zinc-aluminum-magnesium high-strength IF steel. Examples include work hardening indices of 0.19, 0.20, 0.21, 0.22, etc. Plastic strain ratio: The ratio of the true strain in the width direction to the true strain in the thickness direction when a sheet is under uniaxial tension. A plastic strain ratio ≥ 1.85 indicates that zinc-aluminum-magnesium high-strength IF steel mainly undergoes width shrinkage under stress, while exhibiting strong resistance to thickness reduction. Examples include plastic strain ratios of 1.85, 1.90, 1.95, 2.00, etc.

[0047] Figure 1 This is a flowchart illustrating a method for preparing zinc-aluminum-magnesium high-strength IF steel for automotive outer panels, as provided in an embodiment of this application.

[0048] Please see Figure 1 Secondly, this application provides a method for preparing the zinc-aluminum-magnesium high-strength IF steel described in the first aspect, the method comprising: S1. Continuously cast molten steel with the following chemical composition to obtain a billet: C≤0.003%, Si≤0.008%, Mn: 0.90%~1.30%, P: 0.050%~0.085%, S≤0.015%, Nb: 0.010%~0.045%, Ti: 0.01%~0.04%, Als: 0.025%~0.045%, with the remainder being Fe and unavoidable impurities; S2. The billet is heated, rough rolled, finish rolled and coiled in sequence to obtain a hot-rolled coil; S3. The hot-rolled coil is sequentially pickled and cold-rolled to obtain a cold-rolled coil; the total reduction rate of the cold rolling is 55%~80%. S4. The cold-hardened roll is continuously annealed to obtain an annealed plate; the continuous annealing includes a pre-oxidation section, a heating section, a soaking section, a slow cooling section, a rapid cooling section, and an over-aging section; S5. The annealed plate is subjected to continuous hot-dip galvanizing, cooling and finishing in sequence to obtain zinc-aluminum-magnesium high-strength IF steel.

[0049] The pre-oxidation section is implemented in a pre-oxidation chamber located at the inlet of the continuous annealing furnace. The strip steel enters the pre-oxidation chamber at room temperature to 200℃ and exits at 650℃ to 750℃. The pre-oxidation chamber is equipped with: Upper and lower steam injection pipe array, pipe spacing 200mm~300mm, injection orifice diameter 1mm~2mm; Online dew point monitor with a monitoring accuracy of ±1℃ and a response time of ≤5s; Infrared radiation heating element, used to compensate for local temperature drop caused by steam injection; An airtight isolation gate is used for atmosphere isolation between the pre-oxidation chamber and the heating section.

[0050] In some embodiments, the heating temperature is 1220°C to 1260°C, and the total heating time is 180 min to 260 min.

[0051] The heating temperature is controlled between 1220℃ and 1260℃, and the total heating time is controlled between 180 min and 260 min to ensure that microalloying strengthening elements such as Nb and Ti are fully dissolved in austenite, achieving composition homogenization and reserving the necessary elements for the subsequent dispersed precipitation of precipitates. For example, the heating temperature can be 1220℃, 1230℃, 1240℃, 1250℃, 1260℃, etc.; and the total heating time can be 180 min, 200 min, 220 min, 240 min, 260 min, etc.

[0052] In some embodiments, the finishing rolling temperature is 910°C to 950°C.

[0053] The finishing rolling temperature is controlled between 910℃ and 950℃ to obtain fine primary austenite grains, creating conditions for the final refinement of the ferrite microstructure. This finishing rolling temperature range ensures that rolling takes place within the complete austenite recrystallization region, and the dynamic recrystallization process effectively refines the austenite grains. The refined austenite grains transform into fine ferrite grains during subsequent cooling. A uniform and fine ferrite grain structure is the microscopic basis for obtaining a uniform and smooth surface morphology. For example, the finishing rolling temperature can be 910℃, 920℃, 930℃, 940℃, 950℃, etc.

[0054] In some embodiments, the winding temperature is 580°C to 650°C.

[0055] The winding temperature is controlled between 580℃ and 650℃, a temperature range that promotes the formation of numerous fine, dispersed precipitates such as Nb(C,N) and TiC. These precipitates significantly improve the strength of the steel matrix. Simultaneously, the uniform distribution of precipitates helps stabilize the microstructure and reduce microscopic inhomogeneities. For example, the winding temperature can be 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃, or 650℃.

[0056] In some embodiments, the total reduction rate of the cold rolling is 55% to 80%.

[0057] The total reduction rate of cold rolling is controlled between 55% and 80%. This reduction rate provides sufficient driving force for the annealing and recrystallization process and improves the uniformity of the microstructure. For example, the total reduction rate of cold rolling can be 55%, 60%, 65%, 70%, 75%, 80%, etc.

[0058] In some embodiments, the continuous annealing rate is 90 m / min to 120 m / min.

[0059] The continuous annealing speed is controlled between 90 m / min and 120 m / min to coordinate the overall heat treatment time and ensure the full realization of the functions of each process stage. This speed range ensures that the cold-rolled coil has sufficient time to form an effective surface oxide layer in the pre-oxidation temperature range, while also ensuring that the steel matrix can complete sufficient recrystallization and carbide precipitation, among other microstructural transformations. For example, the continuous annealing speed can be 90 m / min, 100 m / min, 110 m / min, 120 m / min, etc.

[0060] In some embodiments, the pre-oxidation section uses high-temperature steam, the dew point of the pre-oxidation section is -35°C to -20°C, and the temperature of the pre-oxidation section is 650°C to 750°C. The dew point (T) dThe temperature (T) satisfies: Td = -(0.65 - 1.83) × 10 -8 T 3.3 .

[0061] The pre-oxidation section uses high-temperature steam, with the dew point controlled between -35℃ and -20℃ and the temperature controlled between 650℃ and 750℃. The dew point and temperature satisfy the following relationship: Td = -(0.65 - 1.83) × 10⁻¹⁰ -8 T 3.3 The purpose of this process is to precisely generate a dense surface iron oxide film that selectively inhibits the migration of P and Mn. By precisely matching the low dew point oxidation atmosphere and temperature, a thin and continuous iron oxide layer can be generated in situ on the surface of the annealed plate. As a physical diffusion barrier, the iron oxide layer effectively blocks the migration of P and Mn from the steel matrix to the surface, fundamentally eliminating the root cause of P and Mn segregation on the surface and the formation of microscopic defects. For example, the dew point of the pre-oxidation stage can be -35℃, -30℃, -25℃, -20℃, etc.; the temperature of the pre-oxidation stage can be 650℃, 700℃, 750℃, etc.

[0062] In some embodiments, the temperature of the heating section is 750℃~790℃; the temperature of the heat spreader section is 750℃~790℃; the temperature of the slow cooling section is 670℃~690℃; the temperature of the rapid cooling section is 460℃~480℃; and the temperature of the over-aging section is 400℃~480℃.

[0063] The temperatures in the heating and soaking zones allow for complete recrystallization of the annealed steel, resulting in uniform and fine ferrite grains. The temperatures in the slow and rapid cooling zones control the cooling path, preventing the formation of undesirable phase transformation products. The over-aging process promotes the full precipitation of dissolved carbon as fine carbides, stabilizing the microstructure, completely eliminating the aging tendency of zinc-aluminum-magnesium high-strength IF steel, and ensuring the stability of its formability. For example, the temperature of the heating section can be 750℃, 760℃, 770℃, 780℃, 790℃, etc.; the temperature of the soaking section can be 750℃, 760℃, 770℃, 780℃, 790℃, etc.; the temperature of the slow cooling section can be 670℃, 680℃, 690℃, etc.; the temperature of the rapid cooling section can be 460℃, 470℃, 480℃, etc.; and the temperature of the over-aging section can be 400℃, 420℃, 440℃, 460℃, 480℃, etc.

[0064] In some embodiments, the temperature of the zinc bath during continuous hot-dip galvanizing is 440°C to 460°C.

[0065] The temperature of the zinc bath in continuous hot-dip galvanizing is controlled between 440℃ and 460℃. This temperature range is significantly higher than the melting point of the zinc-aluminum-magnesium (ZAM) bath, ensuring excellent fluidity and wettability. The ZAM bath can then be evenly spread on a clean, moderately reactive steel substrate surface after the pre-oxidation stage. For example, the zinc bath temperature for continuous hot-dip galvanizing can be 440℃, 450℃, or 460℃.

[0066] In some embodiments, the cooling is post-plating cooling, and the final temperature of the cooling is 250°C to 270°C.

[0067] Cooling is post-plating cooling, with the final cooling temperature controlled between 250℃ and 270℃. This final temperature ensures complete solidification of the zinc-aluminum-magnesium coating and the formation of the desired fine microstructure, thus locking in the excellent corrosion resistance of the zinc-aluminum-magnesium coating. Secondly, this final temperature ensures that the zinc-aluminum-magnesium high-strength IF steel enters a well-balanced state of hardness and plasticity during subsequent finishing processes. This state avoids the problem of the coating becoming too soft and easily damaged due to excessively high temperatures, and also prevents the problem of excessive deformation resistance of the zinc-aluminum-magnesium high-strength IF steel due to excessively low temperatures. For example, the final cooling temperature can be 250℃, 260℃, 270℃, etc.

[0068] In some embodiments, the elongation of the finishing process is 1.3% to 1.5%.

[0069] The elongation of the finishing process is controlled between 1.3% and 1.5%. This range effectively eliminates minor yield plateaus that may exist after annealing and galvanizing, resulting in more uniform mechanical properties for the zinc-aluminum-magnesium high-strength IF steel. Simultaneously, this finishing process significantly improves the flatness of the zinc-aluminum-magnesium high-strength IF steel sheet, eliminating waviness and warping, and ultimately ensuring that the zinc-aluminum-magnesium high-strength IF steel possesses an excellent surface appearance, consistent coating adhesion, and good assembly dimensional accuracy. For example, the elongation of the finishing process can be 1.3%, 1.4%, or 1.5%.

[0070] By controlling the elongation rate of the finishing process within the range of 1.3% to 1.5%, the following surface quality indicators can be achieved: (1) Surface roughness Ra: 0.4μm~0.8μm, which meets the surface roughness requirements before painting the outer panel of the car (Ra≤1.0μm). (2) Gloss (60° incident angle): ≥85GU, to ensure a high gloss effect on the appearance after coating; (3) Elimination of yield plateau: continuous yielding after finishing, with yield point elongation ≤0.1%, to avoid Lüders bands during stamping; (4) Plate shape improvement: After finishing, the wavy height is ≤3mm / m and the warping amount is ≤2mm / m, which meets the plate shape requirements of the automatic stamping line.

[0071] Relationship between finishing elongation and surface roughness: Elongation 1.3%: Ra≈0.75μm, suitable for outer panels of hair hoods with higher formability requirements; With an elongation of 1.4% and Ra≈0.60μm, it exhibits the best overall performance and is suitable for most automotive outer panel parts. With an elongation of 1.5% (Ra≈0.45μm), it boasts the highest surface quality and is suitable for top cover panels requiring extremely high gloss.

[0072] Finishing process parameters may include: Finishing rolling force: 8000kN~12000kN; Roughness of the finishing roller: Ra 2.0μm~3.5μm; Material of the finishing roller: chrome-plated alloy steel, hardness HRC 62~65; Finishing lubricant: Water-based lubricant, concentration 3%~5%.

[0073] The product prepared by the method of preparing zinc-aluminum-magnesium high-strength IF steel is the aforementioned zinc-aluminum-magnesium high-strength IF steel. Since the method of preparing zinc-aluminum-magnesium high-strength IF steel adopts some or all of the technical solutions of the embodiments of zinc-aluminum-magnesium high-strength IF steel, it has at least all the beneficial effects brought about by the technical solutions of the aforementioned embodiments, which will not be elaborated here.

[0074] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards / industry standards / the disclosure herein; if there are no corresponding national standards / industry standards / the disclosure herein, they are performed according to generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer.

[0075] The chemical composition (mass percentage / %) of the examples and comparative examples is shown in Table 1.

[0076] Table 1

[0077] Based on the chemical composition of the embodiments and comparative examples, this embodiment also provides a method for preparing zinc-aluminum-magnesium high-strength IF steel for automotive outer panels, including the following steps: The molten steel with the chemical composition described in Table 1 was continuously cast to obtain a billet; The billet is heated, rough rolled, finish rolled and coiled in sequence to obtain a hot-rolled coil; Hot-rolled coils are pickled and cold-rolled sequentially to obtain cold-hardened coils; The cold-rolled steel sheet is continuously annealed to obtain an annealed sheet; the continuous annealing process includes a pre-oxidation section, a heating section, a soaking section, a slow cooling section, a rapid cooling section, and an over-aging section. The annealed sheet was sequentially subjected to continuous hot-dip galvanizing, cooling, and finishing to obtain zinc-aluminum-magnesium high-strength IF steel. The process parameters are shown in Tables 2 to 4.

[0078] The hot rolling process and the thickness of the hot-rolled coil in the examples and comparative examples are shown in Table 2.

[0079] Table 2

[0080] The process parameters for the examples and comparative examples are shown in Table 3.

[0081] Table 3

[0082] The process parameters for the examples and comparative examples are shown in Table 4.

[0083] Table 4

[0084] The performance of the examples and comparative examples is shown in Table 5. When evaluating the surface quality of the examples and comparative examples, the sample size was 10cm×10cm, and the total number of slag spots (diameter > 0.3mm) and bright spots in this area was counted: a total number of <3 was excellent, a total number of 3 to 5 was good, and a total number of >5 was poor.

[0085] Table 5

[0086] The data tables above provide a clear comparison of the differences between various embodiments and comparative examples. The following conclusions can be drawn: As can be seen from the data in Table 5, the zinc-aluminum-magnesium high-strength IF steel provided in this application embodiment has a yield strength of 270MPa~292MPa, a tensile strength of 402MPa~423MPa, and an elongation after fracture A 80 The surface hardening index is 33%~34.5%, the work hardening index is 0.19~0.2, the plastic strain ratio is 1.9~2.1, and the surface quality is excellent.

[0087] As can be seen from Examples 1-4 and Comparative Examples 1-4, using the composition system and preparation process of this application, Examples 1-4 can stably achieve high strength, high elongation, good formability, and optimal surface quality. However, in Comparative Example 1, because the pre-oxidation temperature was 752°C, which exceeds the optimal range of this application, although the strength and elongation of Comparative Example 1 were acceptable, the surface quality of Comparative Example 1 only reached the good level. Comparative Examples 2-4 did not implement a pre-oxidation stage, and the surface quality of Comparative Examples 2-4 did not reach the optimal level.

[0088] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages: (1) Synergistic design of steel matrix strengthening elements: Through the synergistic design and precise control of four strengthening elements, P, Mn, Nb and Ti, the high strength and high plasticity of zinc-aluminum-magnesium high-strength IF steel were successfully optimized and balanced, avoiding the problem of formability deterioration caused by excessive addition of a single element, and ensuring that zinc-aluminum-magnesium high-strength IF steel can meet the stringent forming requirements of complex stamping parts such as automotive outer panels.

[0089] (2) Characteristics of the multi-element eutectic phase in zinc-aluminum-magnesium coating: The Zn-Al-Mg ternary eutectic phase formed in the zinc-aluminum-magnesium coating not only provides a long-term corrosion resistance that is far superior to that of traditional coatings, but also has low hardness and good plasticity. During the stamping process, it can spread to form a uniform solid lubricating film, effectively reducing the coefficient of friction and improving the stability and surface protection effect of the stamping process.

[0090] (3) Interface regulation effect of pre-oxidation process: The dense iron oxide layer formed on the surface of the steel substrate by the pre-oxidation process effectively prevents the migration and enrichment of elements such as P and Mn to the interface as a physical barrier, and eliminates the surface defects caused by it. The oxide layer also provides an ideal interface for the subsequent hot-dip galvanizing process, promotes the formation of a continuous, uniform and tough Fe-Al transition layer, thereby greatly enhancing the metallurgical bonding strength between the coating and the steel substrate, and fundamentally solving the risk of coating peeling and powdering during the stamping process.

[0091] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.

Claims

1. A zinc-aluminum-magnesium high-strength IF steel for automotive outer panels, characterized in that, The zinc-aluminum-magnesium high-strength IF steel includes a steel substrate and a zinc-aluminum-magnesium coating attached to at least a portion of the surface of the steel substrate. The chemical composition of the steel matrix, by mass fraction, is as follows: C≤0.003%, Si≤0.008%, Mn: 0.90%~1.30%, P: 0.050%~0.085%, S≤0.015%, Nb: 0.010%~0.045%, Ti: 0.01%~0.04%, Als: 0.025%~0.045%, with the remainder being Fe and unavoidable impurities. The chemical composition of the zinc-aluminum-magnesium coating, by mass fraction, is: Al: 1%~3%, Mg: 1%~3%, with the remainder being Zn and unavoidable impurities; The steel substrate surface has an iron oxide layer formed by a pre-oxidation section. The iron oxide layer inhibits the migration of P and Mn to the steel substrate surface and promotes the formation of an Fe-Al bonding layer between the zinc-aluminum-magnesium coating and the steel substrate.

2. The zinc-aluminum-magnesium high-strength IF steel according to claim 1, characterized in that, The microstructure of the zinc-aluminum-magnesium high-strength IF steel includes a ferrite matrix and Nb(C,N) and TiC carbonitride precipitates dispersed in the ferrite matrix.

3. The zinc-aluminum-magnesium high-strength IF steel according to claim 1, characterized in that, The zinc-aluminum-magnesium high-strength IF steel meets at least one of the following properties: yield strength of 260MPa~300MPa, tensile strength of 400MPa~440MPa, and elongation after fracture A. 80 ≥33%, work hardening index ≥0.19, plastic strain ratio ≥1.

85.

4. A method for preparing zinc-aluminum-magnesium high-strength IF steel according to any one of claims 1 to 3, characterized in that, The method includes: Molten steel having the chemical composition described in any one of claims 1 to 3 is continuously cast to obtain a billet; The cast billet is sequentially heated, rough rolled, finish rolled, and coiled to obtain a hot-rolled coil. The hot-rolled coil is sequentially pickled and cold-rolled to obtain a cold-rolled hard coil; the total reduction rate of the cold rolling is 55%~80%. The cold-rolled coil is continuously annealed to obtain an annealed plate; the continuous annealing includes a pre-oxidation section, a heating section, a soaking section, a slow cooling section, a rapid cooling section, and an over-aging section; The annealed sheet is subjected to continuous hot-dip galvanizing, cooling and finishing in sequence to obtain zinc-aluminum-magnesium high-strength IF steel.

5. The method according to claim 4, characterized in that, The heating temperature is 1220℃~1260℃, and the total heating time is 180min~260min; and / or, The finishing rolling temperature is 910℃~950℃; and / or, The winding temperature is 580℃~650℃.

6. The method according to claim 4, characterized in that, The continuous annealing speed is 90 m / min to 120 m / min.

7. The method according to claim 4, characterized in that, The pre-oxidation section uses high-temperature steam, the dew point of the pre-oxidation section is -35℃ to -20℃, and the temperature of the pre-oxidation section is 650℃ to 750℃. The dew point (T) d The temperature (T) satisfies: Td = -(0.65 - 1.83) × 10 -8 T 3.3 .

8. The method according to claim 4, characterized in that, The temperature of the heating section is 750℃~790℃; the temperature of the heat spreader section is 750℃~790℃; the temperature of the slow cooling section is 670℃~690℃; the temperature of the rapid cooling section is 460℃~480℃; and the temperature of the over-aging section is 400℃~480℃.

9. The method according to claim 4, characterized in that, The temperature of the zinc pot for continuous hot-dip galvanizing is 440℃~460℃; The cooling is post-plating cooling, and the final temperature of the cooling is 250℃~270℃.

10. The method according to claim 4, characterized in that, The elongation of the polished surface is 1.3% to 1.5%.